Effect of metal and glycol on mechanochemical dechlorination of polychlorinated biphenyls (PCBs) - Nah, In Wook; Hwang, Kyung-Yub; Shul, Yong-Gun (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
This paper assesses the potential of mechanochemical method with fine metal powder, glycol and alka for polychlorinated biphenyls (PCBs) removal from waste insulating oil. The effects of relevant parameters, such as kinds of chemicals, rate and time of milling were examined. After each run, the total PCB content in waste insulating oil was measured. Polyethylene glycol 200, long chain-glycol was more effective than triethylene glycol and ethylene glycol, short chain-glycol as hydrogen donor in mechanochemical dechlorination of PCBs. A maximum of 99.9% PCBs removal (below 2 ppm) and 94% total chlorin removal were achieved with the mechanochemical process for 2 h. (c) 2008 Elsevier Ltd. All rights reserved.